Quantitative breast lesion classification based on multichannel distributions in shear-wave imaging. Issue 3 (December 2015) - Lo, Chung-Ming; Lai, Yi-Chen; Chou, Yi-Hong; Chang, Ruey-Feng
Highlights: A computer-aided diagnosis (CAD) system based on the quantified color distributions in shear wave elastography (SWE) was developed. The combination of the proposed CAD system using SWE features and BI-RADS assessment would provide a promising diagnostic suggestion. Spatial correlation was combined with the kPa-weighted color information as a feature to reduce the influence of noises far from tumor. Abstract: Background and objectives: A computer-aided diagnosis (CAD) system based on the quantified color distributions in shear-wave elastography (SWE) was developed to evaluate the malignancies of breast tumors. Methods: For 57 benign and 31 malignant tumors, 18 SWE features were extracted from regions of interest (ROI), including the tumor and peritumoral areas. In the ROI, a histogram in each color channel was described using moments such as the mean, variance, skewness, and kurtosis. Moreover, three color channels were combined as a vector to evaluate tissue elasticity. The SWE features were then combined in a logistic regression classifier for breast tumor classification. Results: The performance of the CAD system achieved an accuracy of 81%. Combining the CAD system with a BI-RADS assessment obtained an Az improvement from 0.77 to 0.89 ( p -value <0.05). Conclusions: The combination of the proposed CAD system based on SWE features and the BI-RADS assessment would provide a promising diagnostic suggestion.